2018
DOI: 10.3329/bjb.v47i3.38712
|View full text |Cite
|
Sign up to set email alerts
|

Fruit, seed and pollen morphology of Chorispora DC. species (Brassicaceae) of Turkey

Abstract: Detailed description of fruit, seed and pollen macro-and micromorphological characters of Turkish Chorispora species are provided with illustrations. Typical fruits are linear, straight or strongly curved upward. Nonglandular and glandular trichomes are present or absent. Seeds varied in shape from oblong, oblong-broadly elliptic to subglobose and winged at the apex and base or not. The pollen grains are tricolpate and the basic shape of the pollen grains in species studied is perprolate. The surface sculpturi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…While S. mucronata has the shortest colpus, smallest lumen and psilolumina lumen sculpture. This is supported by (22) where they reported that the width of lumina and muri was considered as one of the characters by which Malcolmia, Strigosella and Zuvanda species could be distinguished.…”
Section: Discussionmentioning
confidence: 74%
“…While S. mucronata has the shortest colpus, smallest lumen and psilolumina lumen sculpture. This is supported by (22) where they reported that the width of lumina and muri was considered as one of the characters by which Malcolmia, Strigosella and Zuvanda species could be distinguished.…”
Section: Discussionmentioning
confidence: 74%
“…The Brassicaceae is a stenopalynous family and morphopalynological attributes confirms homogenous nature of the family (Gabr, 2018a(Gabr, , 2018bMutlu & Erik, 2012). Satil, Kaya, and Ünal (2018)) identified that ornamentation of pollen was reticulate and tricolpate in the family.…”
Section: Discussionmentioning
confidence: 79%
“…Karaismailoğlu (2019) identified the surface ornamentation as tuberculate-reticulate in C. bursa-pastoris seed. Satil et al (2018) stated that the surface ornaments of some species belonging to the genus Chorispora (Brasicaceae) were irregular reticulate. According to SEM images taken from the leaves of C. bursapastoris plant, the epidermis cells on the lower of the leaf had wavy walls, they didn't have a certain shape and dense wax formation was observed on the surface.…”
Section: Findings and Discussionmentioning
confidence: 99%